Training Program as a Moderator for Enhancing the Influence of Service Quality on Hajj Decision-Making at ESQ Tours and Travel - El Medinah, Syamsa; Maulidizen, Ahmad (Jurusan Akuntansi Politeknik Negeri Bandung, 2025)
The Hajj pilgrimage stands as the fifth cornerstone of Islam, defined linguistically as a deliberate engagement in noble or virtuous acts. Technically, it entails the pilgrimage to the Kaaba to fulfill specific rituals and is obligatory for capable and willing Muslims, spanning from the 9th to the 13th of Dhu al-Hijjah. With Indonesia hosting the world's largest Muslim population, Saudi Arabia, as the Hajj pilgrimage's host and organizer, sets limitations or quotas for each Hajj season. ESQ Tours and Travel, among the Hajj travel agencies in Indonesia, specializes in offering tailored Hajj services. This research endeavors to scrutinize the impact of service quality on the decision to embark on the Hajj pilgrimage with ESQ Tours and Travel, incorporating the moderating variable of training programs. Employing a quantitative research approach, data is collected via a questionnaire distributed through Google Forms and managed using Smart-PLS 3. The study's population comprises 915 individuals, with a sample of 90 respondents selected using a nonprobability sampling technique—these respondents being Hajj pilgrims registered with ESQ Tours and Travel in 2022. The research findings reveal an R-Square value of 0.754, representing 75.4%, indicating a significant influence of service quality and training programs on the purchasing decision, with a robust effect. Specifically, the study underscores the substantial and positive impact of service quality and training programs on the purchasing decision. However, it concludes that there is no moderating effect of training programs on the relationship between service quality and the purchasing decision